Preparation method and application of nitrogen-doped highly-graphitized coconut shell carbon material
The nitrogen-doped highly graphitized coconut shell activated carbon material prepared by hard template method and instantaneous Joule heating technology solves the problem of poor catalytic activity of existing carbon materials in electrocatalytic redox reactions, and achieves efficient catalysis and long-term stability.
Patent Information
- Application Number
- CN202411446217.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-10-16
AI Technical Summary
In the electrocatalytic redox reduction reaction, existing non-metal heteroatom doped carbon materials have problems such as low porosity, small specific surface area, few exposed active sites, and difficulty in charge transfer, resulting in poor catalytic activity.
The hard template method was used to pyrolyze the mixed precursor of coconut shell activated carbon, bamboo charcoal or soft charcoal with 2,6-diaminopyridine, NaCl and ZnCl2, and then, nitrogen-doped highly graphitized coconut shell activated carbon materials with greater defects and higher graphitization were prepared by transient Joule heating technology.
The specific surface area and pore content of the material are improved, the graphitization degree and electrocatalytic activity of carbon materials are enhanced, and the efficient catalytic oxygen reduction reaction is achieved, which shows long-term stability for metal air batteries.
Smart Images

Figure CN119542440A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a nitrogen-doped highly graphitized coconut shell carbon material, a preparation method thereof and an electrocatalytic application thereof. Background Art
[0002] The huge energy consumption has triggered an energy crisis based on fossil fuels, leading to a growing interest in renewable clean energy storage and conversion systems. Among various energy conversion devices, zinc-air batteries have attracted much attention due to their safety, high energy density and commercial feasibility. However, there are many challenges in developing effective electrocatalysts for high-performance zinc-air batteries. Biomass carbon-based materials have the advantages of wide sources, low cost, and controllable structure, and have become a hot topic in current research. At the same time, biomass carbon materials obtained by high-temperature pyrolysis of biomass materials have the advantages of high porosity, large specific surface area, good chemical stability and environmental friendliness. Therefore, they are considered to be potential substitutes for metal-based catalysts in the field of electrocatalysis, which can effectively reduce the use of precious metals. Therefore, it is of great significance to study biomass carbon-based materials as electrocatalytic oxygen reduction catalysts and apply them to zinc-air batteries.
[0003] Topological or edge defects in carbon materials, such as pentagonal and heptagonal carbon defects, can accelerate charge transfer during the reaction and change the electronic effect, thereby providing catalytic active sites for the electrocatalytic oxygen reduction reaction. Introducing more defect structures into the carbon substrate will change the local electron redistribution in the carbon material, causing changes in its internal geometry and electronic structure, thereby increasing the number of active sites contained in the material itself, thereby achieving the purpose of optimizing the electrocatalytic performance of the carbon material itself. Therefore, introducing and regulating defects into carbon materials is an important research direction for the preparation of electrocatalytic oxygen reduction catalysts.
[0004] Converting non-metallic heteroatom doping sites into carbon defects is an effective strategy to construct advanced metal-free carbon-based electrocatalysts for oxygen reduction reaction. However, precisely controlling the configuration transformation to achieve highly active oxygen reduction catalysts remains a huge challenge. The addition of heteroatoms to the carbon skeleton can render inert carbon electrocatalytically active for oxygen reduction reaction by significantly disrupting its charge distribution balance and inducing charge delocalization. Based on the heteroatom doping activation strategy, a variety of heteroelement-doped carbon materials have been prepared, including N, B, F, S and P, and showed significant activity for electrocatalytic oxygen reduction reaction. However, non-metallic heteroatom-doped carbon materials often have the problem of low porosity, resulting in a small specific surface area, few exposed active sites, and difficult charge transfer, which ultimately leads to poor catalytic activity. Summary of the invention
[0005] The present invention discloses a nitrogen-doped highly graphitized coconut shell activated carbon material (NC D) preparation method and application, the nitrogen content in the material is 2-3at.%, the pore size distribution is 2-5nm, and the specific surface area is 1526m 2 / g. Using coconut shell activated carbon, bamboo charcoal or softwood charcoal as the carbon source and 2,6-diaminopyridine as the nitrogen source, the mixed precursor was pyrolyzed by the hard template method, and then the nitrogen-doped carbon material with greater defects and higher graphitization was prepared by transient Joule heating. 2 and 2,6-diaminopyridine are dispersed in deionized water, the mixture is heated and stirred to evaporate the water, the precursor is pyrolyzed by a tube furnace annealing process, the remaining metal salts in the pyrolysis material are washed with dilute sulfuric acid for multiple times, and then the graphitization degree and defect degree of the material are enhanced by instantaneous Joule heating process to prepare a natural biomass carbon catalyst with high catalytic performance. NaCl and ZnCl 2 As a hard template, it increases the specific surface area and pore content of the material and promotes graphitization; annealing at high temperature with instantaneous Joule heat further enhances the graphitization degree of the carbon material and forms an N configuration with high electrochemical performance. The prepared nitrogen-doped carbon material can be used for efficient catalytic oxygen reduction reaction and used in metal-air batteries.
[0006] The object of the present invention is to provide a NC D Preparation method. A two-step method is used for preparation, secondary annealing is used, and a tube furnace and instantaneous Joule heating technology are used to achieve the preparation effect. The present invention provides a secondary annealing process to NC D For the four-electron oxygen reduction reaction (4e - First, coconut shell activated carbon, bamboo charcoal or softwood charcoal, 2,6-diaminopyridine, NaCl and ZnCl 2 The precursor was dispersed in deionized water and dried by magnetic stirring under heating to obtain a uniformly mixed precursor. The dried precursor was then heated in N 2 The first high-temperature annealing in a tubular furnace was carried out in a protective atmosphere. During the high-temperature annealing in the tubular furnace, on the one hand, the molten NaCl was inserted into the carbon layer and produced a stress effect, which promoted the formation of carbon defects. On the other hand, Zn, as a template, sublimated during the heating process, removed and reconstructed the configuration of carbon atoms, which was conducive to the formation of carbon defects and the doping of nitrogen atoms. The material annealed in the tubular furnace was ultrasonically washed with dilute sulfuric acid multiple times to completely wash away the remaining metal salts, and then washed with deionized water to neutrality. Subsequently, a second instantaneous high-temperature annealing treatment was carried out using an instantaneous Joule heating device. During the instantaneous Joule heat high-temperature annealing, the graphitization degree of the carbon material was further enhanced, and a N configuration with high electrochemical performance was formed, thereby obtaining a nitrogen-doped highly graphitized coconut shell activated carbon material. This material has a good effect on 4e - The ORR process is highly active and has been applied to metal-air batteries, showing long-term stability.
[0007] The technical solution of the present invention is: a nitrogen-doped highly graphitized coconut shell activated carbon material NC D The N content in the material reaches 2-3 at.%, the pore size distribution is 2-5 nm, and the specific surface area is 1526 m 2 / g, using coconut shell activated carbon, bamboo charcoal or softwood charcoal as carbon source, 2,6-diaminopyridine as nitrogen source, NaCl and ZnCl 2 As a hard template, the mixed precursor was annealed in a tube furnace at high temperature, and then NC with a larger degree of defects and higher graphitization was prepared by transient Joule heating. D Under the conditions of instantaneous Joule heat and high temperature annealing, the graphitization degree of the carbon material is further enhanced, forming an N configuration with high electrochemical performance.
[0008] Preparation of the nitrogen-doped highly graphitized coconut shell activated carbon material NC according to claim 1 D The method comprises the following steps: the carbon source is coconut shell activated carbon, bamboo charcoal or soft wood charcoal, the nitrogen source is 2,6-diaminopyridine, and the defect hard template is NaCl and ZnCl 2 The mixed precursor is subjected to high temperature annealing in a tubular furnace, and then a nitrogen-doped carbon material with a greater degree of defects and higher graphitization is prepared by instantaneous Joule heating. Under the condition of instantaneous Joule heat high temperature annealing, the graphitization degree of the carbon material is further enhanced to form an N configuration with high electrochemical performance. The specific steps are:
[0009] Step 1: Prepare the precursor: Coconut shell activated carbon, bamboo charcoal or softwood charcoal, 2,6-diaminopyridine, NaCl and ZnCl 2 Disperse in deionized water to form a mixed solution, heat and stir in a water bath for a long time to evenly mix the carbon source, nitrogen source and defect template, heat and stir the mixed solution in a water bath to evaporate the water, and thoroughly dry the evaporated solid, and then grind the bulk solid into fine powder to obtain a precursor;
[0010] Step 2: Preparation of NC D : Under the protection of non-reactive gas, the above precursor is subjected to high temperature annealing in a tube furnace, followed by acid washing to remove metal salts in the material, water washing to neutrality, suction filtration and vacuum drying, and the dried tube furnace high temperature annealing material is subjected to secondary high temperature annealing through an instantaneous Joule heating device to prepare NC D .
[0011] The mass ratio of carbon source:nitrogen source:defect template used was 1:1:5:0.5.
[0012] In step 1, the water bath temperature is 100° C., the stirring condition is 450 rpm, and the stirring time is 12-16 h.
[0013] In step 1, the drying temperature is 80°C and the drying time is 10h-12h.
[0014] The first annealing process in step 2 uses a tube furnace with a non-reactive gas of N 2 .
[0015] In the first annealing process in step 2, the heating rate is 5°C / min, the annealing temperature is 1000°C, and the annealing time is 2h.
[0016] In step 2, the acid washing is to use 0.5M dilute sulfuric acid to ultrasonically wash multiple times to remove excess metal salts and wash with deionized water until neutral, and then use a 0.45um filter membrane for suction filtration. The washed and filtered material is dried in an oven at a temperature of 80°C for 12-16 hours.
[0017] In step 2, the secondary high temperature annealing process uses an instantaneous Joule heating device, and the non-reactive gas is Ar; in the instantaneous Joule heating annealing process, the current is: 20A, the heating rate is: 800℃ / s, the annealing temperature is: 700℃-800℃, and the annealing time is: 1s.
[0018] The NC D Applications in electrocatalytic oxygen reduction reaction and metal-air batteries.
[0019] Beneficial effects:
[0020] 1. The preparation method of the present invention is simple, the N content in the material is 2-3at.%, the pore size distribution is 2-5nm, and the specific surface area is 1526m 2 / g, while taking into account the heteroatom structure of the material, the inherent excellent electrochemical conductivity of carbon nanomaterials is maintained, making it have an excellent catalytic effect in electrocatalytic oxygen reduction reaction.
[0021] 2. A two-step preparation method is used to produce a nitrogen-doped highly graphitized coconut shell activated carbon structure, which is simple and efficient. The present invention uses coconut shell activated carbon, bamboo charcoal or soft wood charcoal as a carbon source and 2,6-diaminopyridine as a nitrogen source. The mixed precursor is pyrolyzed by a hard template method, and then a nitrogen-doped carbon material with a greater degree of defects and higher graphitization is prepared by instantaneous Joule heating. Coconut shell activated carbon, bamboo charcoal or soft wood charcoal, NaCl, ZnCl 2 and 2,6-diaminopyridine are dispersed in deionized water, the mixture is heated and stirred to evaporate the water, the precursor is annealed in a tube furnace to pyrolyze the precursor, acid-washed several times to remove the remaining metal salts in the pyrolyzed material, and then the instantaneous Joule heating process is used to enhance the graphitization degree and defect degree of the material to prepare a natural biomass carbon catalyst with high catalytic performance. NaCl and ZnCl 2As a hard template, it increases the specific surface area and pore content of the material and promotes graphitization; instantaneous Joule heat high-temperature annealing further enhances the graphitization degree of the carbon material and forms an N configuration with high electrochemical performance. The prepared nitrogen-doped carbon material can be used for efficient catalytic oxygen reduction reaction and used in metal-air batteries.
[0022] 3. The nitrogen-doped highly graphitized coconut shell activated carbon material of the present invention electrocatalyzes O 2 Produces H 2 O 2 The average selectivity is only 1%-6%, and the electron transfer number is calculated to be around 3.88, which has a high 4e - The selectivity and catalytic activity (expressed by the size of the disk current in the rotating disk test) are 4.35-5.88 mA, and the half-wave potential E 1 / 2 By changing the precursor carbon source, nitrogen-doped highly graphitized carbon configurations of different biomass carbon materials were prepared to change their electrocatalytic oxygen reduction effects. When bamboo charcoal was used as the carbon source, the half-wave potential E 1 / 2 is 0.868 V. When softwood charcoal is used as the carbon source, the half-wave potential E 1 / 2 The material has excellent electrocatalytic oxygen reduction performance. The material also has excellent methanol resistance and long-term catalytic stability. In the current-time (it) test, the current density of the prepared material decayed to 93.5% within 11 hours, which is better than 89.5% of the commercial Pt / C material. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 For NC D High-resolution transmission electron microscopy (HR-TEM) of the material. According to the data analysis in the figure, NC D It shows a typical biomass-based amorphous carbon material structure, containing abundant pores and short-range ordered lattice lines.
[0024] Figure 2 The Raman spectra of the material are shown in Figure 2. According to the analysis of the figure, compared with the pure carbon material control sample (pure C) and the defect template control sample (pure C D ) and the pure heteroatom introduced control sample (NC), NC D The D-band / G-band intensity ratio of the material is significantly reduced, indicating that the defect template and heteroatom doping work synergistically during the secondary annealing process to enhance the graphitization degree of the material.
[0025] Figure 3 The BET specific surface area data of the material is shown in the figure. The pure carbon material control sample pure C, pure C D, single heteroatom introduced control sample (NC) and one-step tube furnace annealing control sample (NC D '), according to the data analysis in the figure, the material has a large specific surface area and forms a rich porous structure.
[0026] Figure 4 The data of the pore diameter and pore volume of the material are shown in the figure. The distribution of pores in the sizes of 0-2nm, 2-50nm, and >50nm is shown in the figure. According to the data analysis in the figure, the material has formed a rich microporous and mesoporous structure.
[0027] Figure 5 This is a data diagram of the X-ray photoelectron spectroscopy (XPS) spectrum of the material. The figure shows the chemical environment and bonding configuration of the nitrogen atom.
[0028] Figure 6 The LSV electrochemical data of the material are shown in the figure. D 、pure C、pure C D , NC, NC D ' and the disk current intensity of the commercial Pt / C control sample. According to the data analysis in the figure, NC D The material exhibited the highest half-wave potential (0.884 V) and the largest limiting current density (5.88 mA cm -2 ), with extremely high electrocatalytic four-electron oxygen reduction reaction (4e - ORR) catalytic activity.
[0029] Figure 7 The LSV electrochemical data of different carbon sources of the materials are shown in the figure. The disk current intensity of coconut shell activated carbon, bamboo charcoal and cork charcoal as carbon sources is shown in the figure. All materials have excellent electrocatalytic oxygen reduction performance.
[0030] Figure 8 This is a long-term stability data graph of the material. The graph shows the current change of the material tested using a rotating ring disk electrode over a period of 11 hours. According to the data analysis in the graph, NC D The disk current of the material maintains good stability within 11 hours, which is better than the commercial Pt / C control sample.
[0031] Fig. 9 The material is applied to the charge and discharge cycle data of metal-air batteries. Constant current charge and discharge test at 5mA cm -2 The current density was 10 min for each cycle. After 1200 hours, NC D The cell overpotential of the catalyst assembly also showed no obvious change, indicating excellent catalytic stability during continuous ORR and OER cycles. DETAILED DESCRIPTION
[0032] The present invention provides an NC D The preparation method adopts a two-step method, uses secondary annealing, uses a tube furnace and instantaneous Joule heating technology to achieve the preparation effect. The present invention provides a secondary annealing process, NC D For the four-electron oxygen reduction reaction (4e - First, coconut shell activated carbon, bamboo charcoal or softwood charcoal, 2,6-diaminopyridine, NaCl and ZnCl 2 The precursor was dispersed in deionized water and dried by magnetic stirring under heating to obtain a uniformly mixed precursor. The dried precursor was then heated in N 2 The first high-temperature annealing in a tubular furnace was carried out in a protective atmosphere. During the high-temperature annealing in the tubular furnace, on the one hand, the molten NaCl was inserted into the carbon layer and produced a stress effect, which promoted the formation of carbon defects. On the other hand, Zn, as a template, sublimated during the heating process, removed and reconstructed the configuration of carbon atoms, which was conducive to the formation of carbon defects and the doping of nitrogen atoms. The material annealed in the tubular furnace was ultrasonically washed with dilute sulfuric acid multiple times to completely wash away the remaining metal salts, and then washed with deionized water to neutrality. Subsequently, a second instantaneous high-temperature annealing treatment was carried out using an instantaneous Joule heating device. During the instantaneous Joule heat high-temperature annealing, the graphitization degree of the carbon material was further enhanced, and a N configuration with high electrochemical performance was formed, thereby obtaining a nitrogen-doped highly graphitized coconut shell activated carbon material. This material has a good effect on 4e - The ORR process is highly active and has been applied to metal-air batteries, showing long-term stability.
[0033] Using coconut shell activated carbon, bamboo charcoal or softwood charcoal as the carbon source and 2,6-diaminopyridine as the nitrogen source, the mixed precursor was pyrolyzed by a hard template method, and then nitrogen-doped carbon materials (NCs) with greater defects and higher graphitization were prepared by transient Joule heating. D ). Coconut shell activated carbon, bamboo charcoal or cork charcoal, NaCl, ZnCl 2 and 2,6-diaminopyridine are dispersed in deionized water, the mixture is heated and stirred to evaporate the water, the precursor is pyrolyzed by a tube furnace annealing process, the remaining metal salts in the pyrolysis material are washed with dilute sulfuric acid for multiple times, and then the graphitization degree and defect degree of the material are enhanced by instantaneous Joule heating technology to prepare a natural biomass carbon catalyst with high catalytic performance. NaCl and ZnCl 2 As a hard template, it increases the specific surface area and pore content of the material and promotes graphitization; annealing at high temperature under instantaneous Joule heat further enhances the graphitization degree of the carbon material and forms an N configuration with high electrochemical performance. The prepared nitrogen-doped carbon material can be used for efficient catalytic oxygen reduction reaction and used in metal-air batteries. The carbon source used in the material is coconut shell activated carbon, bamboo charcoal or cork charcoal, the nitrogen source is 2,6-diaminopyridine, and the defect template is NaCl and ZnCl2 , the ratio used was 1:1:5:0.5.
[0034] The heating and stirring temperature is 100° C., the stirring condition is 450 rpm, and the stirring time is 12 h-16 h.
[0035] The drying temperature is 80°C and the drying time is 10h-12h.
[0036] The first annealing process uses a tube furnace with a non-reactive gas of N 2 .
[0037] The tubular furnace annealing process has a heating rate of 5°C / min, an annealing temperature of 1000°C, and an annealing time of 2h.
[0038] The washing and filtration process uses 0.5M dilute sulfuric acid and a 0.45um filtration membrane. The washed and filtered material is dried in an oven at 80°C for 12-16 hours.
[0039] The second annealing process uses an instantaneous Joule heating device, and the non-reactive gas is Ar.
[0040] The Joule heat annealing process has a current of 20A, a heating rate of 800°C / min, an annealing temperature of 700°C-800°C, and an annealing time of 1s.
[0041] The NC D The material is used in electrocatalytic oxygen reduction reaction.
[0042] The material is used in the electrocatalytic oxygen reduction reaction. The electron transfer number is calculated to be 3.88, which has a high electrocatalytic four-electron oxygen reduction reaction (4e - ORR) selectivity, catalytic activity (expressed by the size of the disk current in the rotating disk test) is 4.35-5.88 mA, and the half-wave potential E 1 / 2 It is 0.884V.
[0043] Example 1: Nitrogen-doped highly graphitized coconut shell activated carbon material NC D
[0044] 1g coconut shell activated carbon, 1g 2,6-diaminopyridine, 5g NaCl and 0.5g ZnCl 2 Disperse into 150 ml of deionized water, heat and stir at 450 rpm and 100 °C to mix evenly, and evaporate the deionized water. Dry the mixed precursor in an oven at 80 °C, and the dried powder is heated in N 2In a protective atmosphere of gas, the mixture was heated at 1000℃ for 2h in a tube furnace at a heating rate of 5℃ / min. After cooling to room temperature, it was pickled with 0.5M dilute sulfuric acid to remove metal salts, washed with deionized water to neutrality, and then treated with instantaneous Joule heating technology. The treatment conditions were current 20A, heating rate 800℃ / s, heating time 1s, argon atmosphere, and NC was prepared. D The catalytic activity (expressed as the magnitude of the disk current in the rotating disk test) is 5.88 mA / cm 2 , half-wave potential E 1 / 2 It is 0.884V.
[0045] Example 2: Pure carbon material pure C without adding nitrogen source and defect template
[0046] Disperse 1g coconut shell activated carbon into 150ml deionized water, heat and stir at 450rpm and 100℃ to mix evenly, and evaporate the deionized water. Dry the mixed precursor in an oven at 80℃, and the dried powder is heated in N 2 In a protective atmosphere of gas, it was heated at 1000℃ in a tube furnace for 2h, with a heating rate of 5℃ / min. After cooling to room temperature, it was pickled with 0.5M dilute sulfuric acid to remove metal salts, then washed with deionized water to neutrality, and then treated with instantaneous Joule heating technology. The treatment conditions were current 20A, heating rate 800℃ / s, heating time 1s, argon atmosphere, and pure carbon material was prepared. The catalytic activity (expressed by the size of the disk current in the rotating disk test) was 4.35mA / cm 2 , half-wave potential E 1 / 2 It is 0.712V.
[0047] Example 3: Pure C material with defect template effect without nitrogen source added D
[0048] 1g coconut shell activated carbon, 5g NaCl and 0.5g ZnCl 2 Disperse into 150 ml of deionized water, heat and stir at 450 rpm and 100 °C to mix evenly, and evaporate the deionized water. Dry the mixed precursor in an oven at 80 °C, and the dried powder is heated in N 2 In a protective atmosphere of gas, the material was heated at 1000℃ for 2h in a tube furnace at a heating rate of 5℃ / min. After cooling to room temperature, it was pickled with 0.5M dilute sulfuric acid to remove metal salts, then washed with deionized water to neutrality, and then treated with instantaneous Joule heating technology. The treatment conditions were current 20A, heating rate 800℃ / s, heating time 1s, argon atmosphere, and the material pure C with defect template effect without adding nitrogen source was prepared. D The catalytic activity (expressed as the magnitude of the disk current in the rotating disk test) was 4.56 mA / cm 2 , half-wave potential E1 / 2 It is 0.748V.
[0049] Example 4: Single heteroatom introduced material NC without adding defect template
[0050] Disperse 1g coconut shell activated carbon and 1g 2,6-diaminopyridine in 150ml deionized water, heat and stir at 450rpm and 100℃ to mix evenly, and evaporate the deionized water. Dry the mixed precursor in an oven at 80℃, and the dried powder is heated in N 2 In a protective atmosphere of gas, it was heated at 1000℃ in a tube furnace for 2h, with a heating rate of 5℃ / min. After cooling to room temperature, it was pickled with 0.5M dilute sulfuric acid to remove metal salts, then washed with deionized water to neutrality, and then treated with instantaneous Joule heating technology. The treatment conditions were current 20A, heating rate 800℃ / s, heating time 1s, argon atmosphere, and a single heteroatom-introduced NC material without added defect template was prepared. The catalytic activity (expressed by the size of the disk current in the rotating disk test) was 5.16mA / cm 2 , half-wave potential E 1 / 2 is 0.85V.
[0051] Example 5: Material NC without secondary instantaneous Joule heating treatment D '
[0052] 1g coconut shell activated carbon, 1g 2,6-diaminopyridine, 5g NaCl and 0.5g ZnCl 2 Disperse into 150 ml of deionized water, heat and stir at 450 rpm and 100 °C to mix evenly, and evaporate the deionized water. Dry the mixed precursor in an oven at 80 °C, and the dried powder is heated in N 2 The mixture was heated at 1000°C for 2 h in a tube furnace in a protective atmosphere of gas, with a heating rate of 5°C / min. After cooling to room temperature, it was pickled with 0.5M dilute sulfuric acid to remove metal salts, and then washed with deionized water until neutral to prepare NC. D The catalytic activity (expressed as the magnitude of the disk current in the rotating disk test) was 4.46 mA / cm 2 , half-wave potential E 1 / 2 It is 0.886V.
[0053] Example 6: Bamboo charcoal replaces coconut shell activated carbon in NC D Material
[0054] 1g bamboo charcoal, 1g 2,6-diaminopyridine, 5g NaCl and 0.5g ZnCl 2 Disperse into 150 ml of deionized water, heat and stir at 450 rpm and 100 °C to mix evenly, and evaporate the deionized water. Dry the mixed precursor in an oven at 80 °C, and the dried powder is heated in N2 In a protective atmosphere of gas, the mixture was heated at 1000℃ for 2h in a tube furnace at a heating rate of 5℃ / min. After cooling to room temperature, it was pickled with 0.5M dilute sulfuric acid to remove metal salts, then washed with deionized water to neutrality, and then treated with instantaneous Joule heating technology. The treatment conditions were current 20A, heating rate 800℃ / s, heating time 1s, and argon atmosphere to prepare NC with bamboo charcoal as the carbon substrate. D The catalytic activity (expressed as the magnitude of the disk current in the rotating disk test) is 5.60 mA / cm 2 , half-wave potential E 1 / 2 It is 0.868V.
[0055] Example 7: NC of coconut shell activated carbon replaced by softwood charcoal D Material
[0056] 1 g of soft charcoal, 1 g of 2,6-diaminopyridine, 5 g of NaCl and 0.5 g of ZnCl 2 Disperse into 150 ml of deionized water, heat and stir at 450 rpm and 100 °C to mix evenly, and evaporate the deionized water. Dry the mixed precursor in an oven at 80 °C, and the dried powder is heated in N 2 In a protective atmosphere of gas, the NC was heated at 1000℃ for 2h in a tube furnace at a heating rate of 5℃ / min. After cooling to room temperature, it was pickled with 0.5M dilute sulfuric acid to remove metal salts, then washed with deionized water to neutrality, and then treated with instantaneous Joule heating technology. The treatment conditions were current 20A, heating rate 800℃ / s, heating time 1s, argon atmosphere, and NC with cork charcoal as the carbon substrate was prepared. D The catalytic activity (expressed as the magnitude of the disk current in the rotating disk test) is 5.80 mA / cm 2 , half-wave potential E 1 / 2 It is 0.846V.
[0057] Comparative Example 1: Pure carbon material pure C without adding nitrogen source and defect template
[0058] Disperse 1g coconut shell activated carbon into 150ml deionized water, heat and stir at 450rpm and 100℃ to mix evenly, and evaporate the deionized water. Dry the mixed precursor in an oven at 80℃, and the dried powder is heated in N 2In a protective atmosphere of gas, it was heated at 1000℃ in a tube furnace for 2h, with a heating rate of 5℃ / min. After cooling to room temperature, it was pickled with 0.5M dilute sulfuric acid to remove metal salts, then washed with deionized water to neutrality, and then treated with instantaneous Joule heating technology. The treatment conditions were current 20A, heating rate 800℃ / s, heating time 1s, argon atmosphere, and pure carbon material was prepared. The catalytic activity (expressed by the size of the disk current in the rotating disk test) was 4.35mA / cm 2 , half-wave potential E 1 / 2 It is 0.712V.
[0059] Comparative Example 2: Pure C material with defect template effect without nitrogen source added D
[0060] 1g coconut shell activated carbon, 5g NaCl and 0.5g ZnCl 2 Disperse into 150 ml of deionized water, heat and stir at 450 rpm and 100 °C to mix evenly, and evaporate the deionized water. Dry the mixed precursor in an oven at 80 °C, and the dried powder is heated in N 2 In a protective atmosphere of gas, the material was heated at 1000℃ for 2h in a tube furnace at a heating rate of 5℃ / min. After cooling to room temperature, it was pickled with 0.5M dilute sulfuric acid to remove metal salts, then washed with deionized water to neutrality, and then treated with instantaneous Joule heating technology. The treatment conditions were current 20A, heating rate 800℃ / s, heating time 1s, argon atmosphere, and the material pure C with defect template effect without adding nitrogen source was prepared. D The catalytic activity (expressed as the magnitude of the disk current in the rotating disk test) was 4.56 mA / cm 2 , half-wave potential E 1 / 2 It is 0.748V.
[0061] Comparative Example 3: Material NC without adding defect template and single heteroatom introduction
[0062] Disperse 1g coconut shell activated carbon and 1g 2,6-diaminopyridine in 150ml deionized water, heat and stir at 450rpm and 100℃ to mix evenly, and evaporate the deionized water. Dry the mixed precursor in an oven at 80℃, and the dried powder is heated in N 2 In a protective atmosphere of gas, it was heated at 1000℃ in a tube furnace for 2h, with a heating rate of 5℃ / min. After cooling to room temperature, it was pickled with 0.5M dilute sulfuric acid to remove metal salts, then washed with deionized water to neutrality, and then treated with instantaneous Joule heating technology. The treatment conditions were current 20A, heating rate 800℃ / s, heating time 1s, argon atmosphere, and a single heteroatom-introduced NC material without added defect template was prepared. The catalytic activity (expressed by the size of the disk current in the rotating disk test) was 5.16mA / cm2 , half-wave potential E 1 / 2 is 0.85V.
[0063] Comparative Example 4: Material NC without secondary instantaneous Joule heating treatment D '
[0064] 1g coconut shell activated carbon, 1g 2,6-diaminopyridine, 5g NaCl and 0.5g ZnCl 2 Disperse into 150 ml of deionized water, heat and stir at 450 rpm and 100 °C to mix evenly, and evaporate the deionized water. Dry the mixed precursor in an oven at 80 °C, and the dried powder is heated in N 2 The mixture was heated at 1000°C for 2 h in a tube furnace in a protective atmosphere of gas, with a heating rate of 5°C / min. After cooling to room temperature, it was pickled with 0.5M dilute sulfuric acid to remove metal salts, and then washed with deionized water until neutral to prepare NC. D The catalytic activity (expressed as the magnitude of the disk current in the rotating disk test) was 4.46 mA / cm 2 , half-wave potential E 1 / 2 It is 0.886V.
[0065] A variety of comparative examples were designed and prepared to compare the nitrogen source, NaCl / ZnCl 2 The effect of defective template, including the pure C comparison ratio without nitrogen source and defective template, pure C without nitrogen source D Comparative example, NC without defect template, and NC without secondary transient Joule heat treatment D 'Comparative Example. By comparison, NC D Due to the treatment of metal Zn and transient Joule heat, the crystallinity of carbon is enhanced, and its high-resolution transmission electron microscopy image also shows the typical biomass-based amorphous carbon material structure, containing abundant pores and short-range ordered lattice lines. Compared with the comparative example, NC D According to Raman characterization data, NC D The D-band / G-band intensity ratio of the material is significantly reduced, indicating that the defect template and heteroatom doping work synergistically during the secondary annealing process to enhance the graphitization degree of the material. From the BET specific surface area data, it can be seen that the addition of nitrogen precursors and metal salts leads to the collapse of the porous structure. The reconstruction of the carbon ring is a normal phenomenon after two annealing treatments in the tubular and Joule furnace. Therefore, NC D The specific surface area of NC D The highest electrocatalytic performance was 4e - The oxygen reduction catalytic activity, the highest half-wave potential (0.884 V), and the highest limiting current density (5.88 mA cm -2 ).
Claims
1. A nitrogen-doped highly graphitized coconut shell activated carbon material NC D , characterized in that, The nitrogen content in the material reaches 2-3 at.%, the pore size distribution is 2-5 nm, and the specific surface area is 1526 m 2 / g, using coconut shell activated carbon, bamboo charcoal or soft wood charcoal as carbon source, 2,6-diaminopyridine as nitrogen source, NaCl and ZnCl2 as hard templates, the mixed precursor was annealed in a tube furnace at high temperature, and then transient Joule heating was used to prepare NC with larger defects and higher graphitization D Under the conditions of instantaneous Joule heat and high temperature annealing, the graphitization degree of the carbon material is further enhanced, forming an N configuration with high electrochemical performance.
2. Preparation of the nitrogen-doped highly graphitized coconut shell activated carbon material NC according to claim 1 D The method is characterized in that The carbon source is coconut shell activated carbon, bamboo charcoal or soft wood charcoal, the nitrogen source is 2,6-diaminopyridine, the defect hard template is NaCl and ZnCl2, the mixed precursor is subjected to high temperature annealing in a tubular furnace, and then a nitrogen-doped carbon material with a greater degree of defects and higher graphitization is prepared by instantaneous Joule heating. Under the condition of instantaneous Joule heat high temperature annealing, the graphitization degree of the carbon material is further enhanced to form an N configuration with high electrochemical performance. The specific steps are: Step 1, preparing a precursor: dispersing coconut shell activated carbon, bamboo charcoal or cork charcoal, 2,6-diaminopyridine, NaCl and ZnCl2 in deionized water to form a mixed solution, heating and stirring in a water bath for a long time to uniformly mix the carbon source, nitrogen source and defect template, heating and stirring the mixed solution in a water bath and evaporating the water, and thoroughly drying the evaporated solid, and then grinding the large solid into fine powder, which is the precursor; Step 2: Preparation of NC D : Under the protection of non-reactive gas, the above precursor is subjected to high temperature annealing in a tube furnace, followed by acid washing to remove metal salts in the material, water washing to neutrality, suction filtration and vacuum drying, and the dried tube furnace high temperature annealing material is subjected to secondary high temperature annealing through an instantaneous Joule heating device to prepare NC D .
3. The method according to claim 2, characterized in that The mass ratio of carbon source:nitrogen source:defect template used was 1:1:5:0.
5.
4. The method according to claim 2, characterized in that In step 1, the water bath temperature is 100° C., the stirring condition is 450 rpm, and the stirring time is 12-16 h.
5. The method according to claim 2, characterized in that In step 1, the drying temperature is 80°C and the drying time is 10h-12h.
6. The method according to claim 2, characterized in that The first annealing process in step 2 uses a tubular furnace and the non-reactive gas is N2.
7. The method according to claim 2, characterized in that In the first annealing process in step 2, the heating rate is 5°C / min, the annealing temperature is 1000°C, and the annealing time is 2h.
8. The method according to claim 2, characterized in that In step 2, the acid washing is to use 0.5M dilute sulfuric acid to ultrasonically wash multiple times to remove excess metal salts and wash with deionized water until neutral, and then use a 0.45um filter membrane for suction filtration. The washed and filtered material is dried in an oven at a temperature of 80°C for 12-16 hours.
9. The method according to claim 2, characterized in that In step 2, the secondary high temperature annealing process uses an instantaneous Joule heating device, and the non-reactive gas is Ar; in the instantaneous Joule heating annealing process, the current is: 20A, the heating rate is: 800℃ / s, the annealing temperature is: 700℃-800℃, and the annealing time is: 1s.
10. The NC according to claim 1 D Applications in electrocatalytic oxygen reduction reaction and metal-air batteries.
Citation Information
Patent Citations
Nitrogen-doped carbon-supported non-noble metal nano-catalyst prepared based on MOF
CN113270595A
Metal-free porous nitrogen-oxygen doped carbon-based catalyst as well as preparation method and application thereof
CN115064706A
Preparation method and application of in-situ activated furfural residue and nitrogen-sulfur co-doped porous carbon catalyst
CN116190686A
Preparation method for high hardness metal layer comprising surface laser remelting process
KR1020230164352A